PENGAWETAN LIMA JENIS KAYU SECARA RENDAMAN DINGIN DENGAN DUA JENIS BAHAN PENGAWET CCB (Cold Soaking Treatment of Five Wood Species Using Two CCB Preservatives) - Sasa Abdurrohim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Wood Samples of five species measuring 3 cm x 3cm x 3cm (200 samples for each species) were treated with cold soaking treatment using Wolmanil CB and Diffusol CB preservatives for 1, 3, 5, 7, and 9 days at the concentrations of 2, 4, 6, and 8 percent,The test result of experiment, after taking both retention and penetration requirements into concideration for wood used under roof, and in the open air both without ground contact, showed that only two species, perupuk and keruing daun lebar, could be satisfactorily treated with Wolmanil CB under the experimental conditions, while other three species, damar kunyil, lanan and dungun, haven 't been meet the standar. Diffusol CB preservative showed a good result only on one species, i. e. perupuk.Keruing daun lebar for under roof and in the open air usage both without ground contact can be consecutively soaked for 7 days in Wolmanit CB solution of 6 and 8 percent, while perupuk, only for under roof without ground contact, for 9 days in 8 percent solution. Perupuk used under roof and in the open air without ground contact could be soaked for 7 days in Diffusol CB solution of 4 and 6 percent.